Effect of Early Feeding Programs on Broiler Performance - Hooshmand, Mohammad (International Journal of Poultry Science, 2006)
This experiment was a 4x2 factorial arrangement of four feeding programs with or without water soluble multivitamin + electrolytes supplementation for the first 3 days of age. Four feeding programs includes: feeding a starter diet immediately after hatch until 28 d of age, feeding a prestarter diet immediately after hatch until 3 d of age, fasting for 24 hours after hatch, or fasting for 12 hours with access to water containing 5% sugar followed by 12 hours corn feeding after hatch. All chicks on the prestarter, fasting, and sugar corn feeding programs were fed the starter diet until 28 d of age after the end of the initial 3 d or 24 h treatment. This was followed by grower and finisher diets for the periods 29 to 42 d and 43 to 48 d, respectively. Feeding program had a significant (p< 0.05) effect on final body weight. No significant (p>0.05) differences were observed in overall feed intake and feed conversion ratio. Supplement had no significant effects on body weight, feed intake, and feed conversion ratio. No interactions were observed between feeding program and supplement for body weight, feed intake, and feed conversion ratio. No significant differences were observed for abdominal fat, and organs weight (except for liver) between feeding programs. Twenty four hours fasting significantly (p< 0.05) reduced T3 concentration. multivitamin + electrolytes supplement significantly (p< 0.05) increased liver weight and T3 concentration.